Dari Kebijakan ke Realitas Kelas: Progresivisme dalam Kurikulum Merdeka di Sekolah Dasar Indonesia - Mufid, Nur; Kun Sumantri; Alynia Purwaning; Endang Fauziati; Maryadi (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2026)
This study critically examines the implementation of the Merdeka Curriculum in Indonesian primary schools through the lens of progressivist educational philosophy, with particular attention to the realization of student-centered learning in classroom practice. Employing a descriptive qualitative design, the study collected data from ten classroom learning videos, ten teaching module documents, and questionnaires administered to teachers with teaching experience ranging from 5 to 20 years. Data were analyzed thematically by identifying patterns related to student autonomy, classroom interaction, and the balance of teacher–student roles. The findings reveal a noticeable discrepancy between policy intentions and classroom realities. Although teachers demonstrated conceptual understanding of progressivist principles and formally integrated student-centered steps into lesson plans, actual classroom practices remained predominantly teacher-dominated. Students were provided limited opportunities to engage in meaningful inquiry, discussion, and reflection, while teachers continued to control the learning process by delivering extensive explanations and directing students toward predetermined answers. This indicates that progressivist values embedded in the Merdeka Curriculum have been implemented at a procedural rather than a philosophical level. The study concludes that without deeper philosophical engagement and sustained professional development, curriculum reform risks becoming a symbolic change that fails to transform classroom culture.